EFEKTIVITAS PENERAPAN MEDIA THINK STACK ECONOMY DENGAN MODEL PEMBELAJARAN KONTEKSTUAL DALAM MENINGKATKAN PEMAHAMAN KONTEKSTUAL SISWA - Khomsatun Nikmatul Husna; Nur Anita Yunikawati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
This study aims to examine the effectiveness of implementing the Think Stack Economy media combined with a contextual teaching and learning model in improving students’ contextual understanding of the topic of Banking and Non-Banking Financial Institutions. This research employed a quantitative approach with a quasi-experimental design, involving an experimental class and a control class at a public senior high school in Kepanjen. Data were collected through written tests in the form of pretests and posttests, then analyzed using the N-Gain test, normality test, Mann-Whitney U test, and Cohen’s d test. The findings reveal that the experimental class, which implemented the Think Stack Economy media with the contextual learning model, achieved a substantially higher improvement in contextual understanding than the control class, with a large effectiveness category. These findings confirm that combining game-based media with a contextual learning model offers an effective and innovative alternative strategy for economics instruction.